АККУМУЛЯЦИЯ ТЯЖЕЛЫХ МЕТАЛЛОВ РАСТИТЕЛЬНОСТЬЮ И ПОЧВОЙ В ЗОНЕ ВЛИЯНИЯ ПРЕДПРИЯТИЙ ВОСТОЧНОЙ ПРОМЫШЛЕННОЙ ЗОНЫ Г. ПАВЛОДАРА (Experimental biology, 2009)
The article рrovides results of research on the level of heavy metals such as Ti, Mn, Cr, Fe, Ni, Cu, Zn, Pb, Sr in the soil and vegetable (Agropyron pectiniforme Roem. et Schult.) samples taken on affected zone of plant of east industrial zone of Pavlodar city
Keywords: Ti; Mn; Cr; Fe; Ni; Cu; Zn; Pb; Sr